2010
DOI: 10.1002/pro.377
|View full text |Cite
|
Sign up to set email alerts
|

Design, selection, and characterization of a split chorismate mutase

Abstract: Split proteins are versatile tools for detecting protein-protein interactions and studying protein folding. Here, we report a new, particularly small split enzyme, engineered from a thermostable chorismate mutase (CM). Upon dissecting the helical-bundle CM from Methanococcus jannaschii into a short N-terminal helix and a 3-helix segment and attaching an antiparallel leucine zipper dimerization domain to the individual fragments, we obtained a weakly active heterodimeric mutase. Using combinatorial mutagenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
(116 reference statements)
0
22
0
Order By: Relevance
“…The 115 amino acid long three-helix fragment Z-C3 was produced recombinantly in a chorismate mutase deficient E. coli strain, thereby excluding the possibility of contamination with endogenous enzyme. [12] Kinetic assay: Kinetic assays were performed by measuring the consumption of chorismate spectroscopically at either 274 nm (e 274 = 2630 m À1 cm…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 115 amino acid long three-helix fragment Z-C3 was produced recombinantly in a chorismate mutase deficient E. coli strain, thereby excluding the possibility of contamination with endogenous enzyme. [12] Kinetic assay: Kinetic assays were performed by measuring the consumption of chorismate spectroscopically at either 274 nm (e 274 = 2630 m À1 cm…”
Section: Methodsmentioning
confidence: 99%
“…An engineered heterodimeric chorismate mutase (CM), [12] which catalyzes the sigmatropic rearrangement of chorismate to prephenate (hdCM; Figure 1 a), served as the protein scaffold for the assembly of hybrid enzymes. hdCM was originally constructed by dissecting the helical-bundle CM from Methanocaldococcus jannaschii into a short N- Figure 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the use of our novel transposase-based library design strategy with thermophilic proteins may represent an effective way to accelerate the discovery of split regulatory proteins that cooperatively function for synthetic biology applications in mesophiles, 17 without the need for further optimization. 33,54 Proteins with enhanced thermostability may also be poised to evolve new structures and functions through fission. A recent study showed that mesophilic protein fragmentation can result in polypeptide fragments that form functional oligomers with a new quaternary structure, 55 reinforcing a long-standing hypothesis that proteins can adapt new structures through the exchange or shuffling of their polypeptide domain.…”
Section: Discussionmentioning
confidence: 99%